A Study on Significant Changes Incorporated in the ITR-1 (SAHAJ) for the Assessment Year 2020-21 under the Income Tax Act, 1961 - Sanjib Ghimire (International Journal of Engineering and Management Research, 2020)
In this paper, an attempt has been made to study the changes that has been incorporated in the recently notified ITR-1 (SAHAJ) for the A.Y. 2020-21 under the Income Tax Act, 1961. A detailed analysis of the amendments that has been made in the income tax laws with respect to filing of the ITR-1 for A.Y. 2020-21 and a comparative analysis between ITR-1 of A.Y. 2019-20 and 2020-21 has revealed that certain noteworthy changes have been incorporated in the ITR-1 for A.Y. 2020-21.Significant changes have been incorporated in the PART A - GENERAL INFORMATION segment and PART C – DEDUCTIONS AND TAXABLE TOTAL INCOME segment besides insertion of a new schedule “Schedule DI – Details of Investment”. The current study has revealed that the CBDT has expanded the scope of disclosure requirements in the ITR-1 which is expected to provide more transparency and reduced litigation with respect to ITRs filed.